Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Explore thousands of questions and answers from a knowledgeable community of experts on our user-friendly platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

Solve: -2(2x+6)= -3x​

Sagot :

hope you find this helpful. :D

View image XpertthiefFan

Answer:

below

Step-by-step explanation:

-2(2x+6)=-3x

1. distribute

-4x-12=-3x

2. add 3x to both sides

-x-12=0

3. add 12 to both sides

-x = 12

4. divide both sides by -x or -1

-x/-1 = 12/-1

ANSWER : x = -12